(untitled) (Journal of Universal Science Research, 2024)
In this article, the historical and scientific schools of management of the field of culture and art, the first past of mankind, the first material and spiritual, cultural settlements were formed in the East and prepared the ground for the further development of mankind. Kohna is the cradle of eastern enlightenment. There is a philosophy of common features and values that keep it united in a holistic way.As long as Uzbekistan is an integral part of the East, it can be seen that the sermulohazakorism of the eastern rings, the desire to be able to make the necessary decisions in existing situations, the meaning of human life –being an example in labor and creativity, avoiding evil, spending life once given on Good Deeds has become the criterion of life of this people.